Canada’s Official Languages Act, Border Imperialism, and the Surface Tension of Water - Martin, Sonia (Language and Literacy / Langue et littératie, 2024)
This paper examines how Canada’s Official Languages Act (OLA) reinforces the socio-political constructs of language barriers and linguistic borders. Questions addressed are: in Canada, who do linguistic borders serve, how do linguistic borders function, and what are the effects of linguistic borders? The theoretical framework draws from raciolinguistics and border imperialism. The method, a socio-diagnostic critique, juxtaposes the discursive practices of the OLA with border governance strategies. Results highlight how linguistic border governance creates the conditions for language-based discrimination to thrive. The paper concludes with a call to disinvest from the OLA, and a turning toward the water-language connection.